A head-to-head comparison of humoral and cellular immune responses of five COVID-19 vaccines in adults in China - Han, Xu; Pan, Hongxing; Jin, Pengfei; Wei, Mingwei; Jia, Siyue; Wang, Wenjuan; Chu, Kai; Gao, Shuyu; Zhou, Li; Li, Jingxin; Zhu, Fengcai (Frontiers in Immunology, 2024)
Various COVID-19 vaccine trials have shown that vaccines can successfully prevent symptomatic cases of help to better understand the immune response characteristics of different COVID-19 vaccines in humans. We randomly selected 20 participants from each of five ongoing Phase Ⅱ trials of COVID-19 vaccines. Here, SARS-CoV-2specific immune responses to DNA vaccine (INO-4800), mRNA vaccine (BNT162b2), Adenovirusvectored vaccine (CONVIDECIA), Protein subunit vaccine (Recombinant COVID-19 Vaccine (Sf9 Cells)), Inactivated Vaccine (KCONVAC) were examined longitudinally in healthy adults between Jan 15, 2021 and July 5, 2021 for 6 months. RBD-IgG titres were detected by ELISA, neutralising antibody titer were detected by pseudoviral neutralization and immune cell response were detected by flow cytometry. At the first visit (V1), 100% of individuals who received the BNT162b2, CONVIDECIA, or KCONVAC vaccines experienced seroconversion of neutralizing and binding antibodies in the serum. Except for the Recombinant COVID-19 Vaccine (Sf9 Cells) vaccine havingthe highest neutralizing antibody GMT at the second visit (although there was no statistically significant difference in geometric mean titers between V1 and V2), the rest of the vaccines had the highest levels of binding antibodies and neutralizing antibodies at V1. The neutralizing antibodies GMT of all vaccines showed a significant decrease at V3 compared to V1. The neutralizing antibody GMT against the omicron variant of all vaccines at V1 showed a significant decrease compared to the wild strain. We observed statistically significant differences in Tcm cells and RBD-specific memory B cells among various vaccines.